Resource Barriers: The Difficulties of Integrating ICT in Teaching-Learning at Tribhuvan University - Joshi, Bishnu Maya; Ghimire, Durga Devi (Nepal Journal of Multidisciplinary Research, 2026)
Background: Integrating Information and Communication Technology (ICT) in education is inevitable in current time. Though, there is less integration of ICT in teaching -learning at university level in Nepalese context. In this context, this study examined the resource barriers experienced by economics teachers at Tribhuvan University in using ICT for teaching-learning activities. Methods: The study was conducted based on quantitative research methodology by using cross-sectional study under descriptive research design. 404 economics teachers of Tribhuvan University were respondents of this study; data were collected self-constructed structured research tools. Data were analyzed through descriptive and inferential statistical tools. Results: The findings, categorized into two theme areas i.e. nature and magnitude of resource barriers and influence of institutional and teachers’ characteristics found that teachers experienced moderate but significant resource barriers, mainly time constraint, inadequate ICT infrastructure, limited computer labs, inconsistent internet connectivity and insufficient classroom ICT facilities. Conclusion: Resource barriers closely mirror to integrate ICT in teaching-learning reported in developing-country contexts. Teachers involved campus type (Constituent and Community) and their academic qualification significantly predicted resource barriers. Teachers of community campuses and those with higher academic qualification experienced higher barriers. Novelty: The study shows that Tribhuvan University still has institutional inequities that need to be fixed. It also shows that legislative changes, targeted funding, and better institutional support mechanisms are needed to make sure that ICT is integrated more fairly and effectively across campuses.